Kinetics of pyrite, pyrrhotite, and chalcopyrite dissolution by Acidithiobacillus ferrooxidans - Kocaman, Ayse Tuba; Cemek, Mustafa; Edwards, Katrina Jane (CANADIAN SCIENCE PUBLISHING, NRC RESEARCH PRESS, 2016)
The main objective of this study was to investigate the dissolution kinetics of pyrite, pyrrhotite, and chalcopyrite. Crushed minerals were reacted with Acidithiobacillus ferrooxidans (25 degrees C). The kinetics of dissolution was investigated by monitoring pH and Fe2+ and Fe3+ ion concentrations in the leaching solutions. Pyrite, pyrrhotite, and chalcopyrite dissolution by A. ferrooxidans was found to be a chemically controlled process. With bacteria, the dissolution rates of the minerals increased in the order of pyrrhotite, pyrite, and chalcopyrite. The number of cells attached to mineral surfaces increased in the same order. Acidithiobacillus ferrooxidans was found to enhance the dissolution rates of the minerals. The acid-insoluble trait of pyrite and acid-soluble trait of the other 2 minerals affected the pH changes in the leaching solutions.
Keywords: Acidithiobacillus ferrooxidans; pyrite; pyrrhotite; chalcopyrite; dissolution kinetics; X-RAY PHOTOELECTRON; HYDROGEN-PEROXIDE; SULFIDE MINERALS; SULFURIC-ACID; FERROUS-IONS; ELECTROCHEMICAL DISSOLUTION; NONOXIDATIVE DISSOLUTION; OXIDATIVE DISSOLUTION; HINDERED DISSOLUTION; BACTERIAL ATTACHMENT; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Immunology; Microbiology